2019
DOI: 10.1002/uog.19101
|View full text |Cite
|
Sign up to set email alerts
|

Image‐scoring system for umbilical and uterine artery pulsed‐wave Doppler ultrasound measurement

Abstract: In quality assessment of umbilical and uterine artery pulsed wave Doppler measurements, an objective six-point image scoring system is associated with greater reproducibility than subjective assessment. We recommend this as the preferred method for quality control, audit and teaching. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…25 Our umbilical artery Doppler measurements quality control methods have previously been published, which include the interobserver variability on a large sample of measurements. 28 ajog.org…”
Section: Standard Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Our umbilical artery Doppler measurements quality control methods have previously been published, which include the interobserver variability on a large sample of measurements. 28 ajog.org…”
Section: Standard Proceduresmentioning
confidence: 99%
“…48 The second limitation was that we did not perform an inter-and intraobserver evaluation. Nevertheless, we have undertaken strict quality assessment using a scoring system that was used in this study and this has been shown to be more reproducible than subjective assessment 28 ; therefore, all possible measures to improve reproducibility have been addressed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A power calculation was performed to evaluate the number of women required to identify optimal reproducibility values. We estimated that a total of 100 images would be required to detect significant differences between two operators, in accordance with calculations from previous studies 18–20 . As a previous study has shown that the CS scar could be visualized in 90% of cases 13 , 55 cases (110 sagittal and transverse images to achieve adequate power) were reviewed for each part of the study.…”
Section: Methodsmentioning
confidence: 77%
“…However, objective quality scoring would be more informative, particularly in a research setting in which interpretation of the results could be highly influenced by the quality of the measurements. A scoring system for MCA Doppler quality was developed by Ruiz-Martinez et al 9 and later adapted for UA and uterine artery Doppler 4 . This objective assessment showed higher inter-rater reliability and agreement than did subjective evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of ultrasound, there are quality control systems aimed at ensuring acceptable levels of reliability among operators and consistency of measurements [1][2][3][4] . This issue is particularly important for the performance of multicenter studies because of their inherent heterogeneity 5 .…”
Section: Introductionmentioning
confidence: 99%